Accidental poisoning with Wedelia glauca (“sunchillo”) in a bull confirmed by analysis of rumen content - Costa, Enrique Félix (2013)
Wedelia glauca is an invasive, perennial plant of the Asteraceae family native to South America. Its toxicity is attributed to the presence of a hepatotoxic terpenoid known as atractyloside, a powerful inhibitor of cellular respiration and ATP synthesis. Cattle are the most frequently poisoned species, and the course of this poisoning is hyperacute or acute. Occasionally, it is possible to find fragments of plants in the rumen contents and indentify the dermis structure of the plants, as they do not undergo significant changes in spite of the mechanic and enzymatic activities occurring in the rumen. The macroscopic and microscopic anatomopathologic findings of a natural Wedelia glauca poisoning case in a Hereford bull are reported. It was confirmed by micrographic analysis of plant fragments found in the rumen contents and also in bales used to feed those animals.